The 50-plus market: the importance of demographics and geodemographics - Rae, John (Henry Stewart Talks, 2009)
Introductory statistics on the 50-plus market, Demographic changes 1991 to 2001, Spending power of the 50-plus, Preferred use of spare time, Segmenting the 50-plus market, The future of the 50-plus market